KNOWLEDGE AND ATTITUDE OF RURAL WOMEN WEAVERS TOWARDS SOCIAL MEDIA MARKETING - DEEKSHITA DUTTA; T. RADHA (The Journal of Research ANGRAU, 2022)
The objective of this research is to find out the level of knowledge of50 women weavers on social media marketing and their attitude towards the same.The study was conducted in the state of Assam between August and September, 2021 and the district Lakhimpur was selected as the study area.Two villages were selected randomly and a sample of 25 weavers were selected from each village,thus, the making total sample size of 50. The main findings of the study revealed that more than half (60%) of the respondents has medium level knowledge on social media marketing and its sites and 40% have unfavourable attitude towards it. However, it is also worth mentioning that nearly equal number of respondents (38%) have favourable attitude. The women weaved different types of fabrics like cotton and silk and some of the noteworthy garments are the traditional mekhe lachadar of Assam and Gamusa.